2019
DOI: 10.3390/foods8090409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Gluten Protein Composition of Ancient (Einkorn, Emmer and Spelt) and Modern Wheat Species (Durum and Common Wheat)

Abstract: The spectrophotometric Bradford assay was adapted for the analysis of gluten protein contents (gliadins and glutenins) of spelt, durum wheat, emmer and einkorn. The assay was applied to a set of 300 samples, including 15 cultivars each of common wheat, spelt, durum wheat, emmer and einkorn cultivated at four locations in Germany in the same year. The total protein content was equally influenced by location and wheat species, however, gliadin, glutenin and gluten contents were influenced more strongly by wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
81
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 24 publications
14
81
2
1
Order By: Relevance
“…As expected, common wheat was associated with glutenins (Geisslitz et al, 2018), whereas ω5-and α-gliadins mostly determined the placement of einkorn cultivars. The results are in agreement with the PCA reported by Geisslitz et al (2019) that also showed an association between glutenin contents and the location of common wheat cultivars, as well as between gliadin contents and einkorn. Our new approach allowed a better differentiation of wheat species than before, but there were also similarities regarding the overlap of spelt, durum wheat, and emmer.…”
Section: Distinction Of Wheat Species Using the New Integration Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, common wheat was associated with glutenins (Geisslitz et al, 2018), whereas ω5-and α-gliadins mostly determined the placement of einkorn cultivars. The results are in agreement with the PCA reported by Geisslitz et al (2019) that also showed an association between glutenin contents and the location of common wheat cultivars, as well as between gliadin contents and einkorn. Our new approach allowed a better differentiation of wheat species than before, but there were also similarities regarding the overlap of spelt, durum wheat, and emmer.…”
Section: Distinction Of Wheat Species Using the New Integration Methodssupporting
confidence: 93%
“…Each gluten protein type contains different numbers of single proteins, for example, 7 ω-gliadins, 23 α-gliadins, 13 γ-gliadins, 5 HMW-GS, and 22 LMW-GS as identified in the wheat cultivar Butte 86 (Dupont, Vensel, Tanaka, Hurkman, & Altenbach, 2011). However, these numbers and the protein quantities vary depending on the genotype (G), the environment (E), and the G × E interaction (Geisslitz, Longin, Scherf, & Koehler, 2019;Shewry et al, 2010;Ward et al, 2008). Usually, the classification into albumins/globulins and gluten protein types is applied for the qualitative and quantitative characterization of wheat proteins by means of reversed-phase (RP)-HPLC, that can be used to elucidate relationships between protein structure, functionality (e.g., baking performance), and bioactivity (e.g., potential to elicit immune reactions) (Schalk, Lexhaller, Koehler, & Scherf, 2017).…”
mentioning
confidence: 99%
“…One limitation of the current study is that the results are based on the analysis of GPTs isolated from one single cultivar of each grain grown in one year. Although the choice of the cultivars was done carefully to select representative samples, genetic and environmental factors and their interaction are known to influence the proteome composition of cereals (Hajas et al, 2018;Juhasz et al, 2018;Malalgoda et al, 2018;Geisslitz et al, 2019). The results obtained here thus only provide one snapshot and are expected to change depending on the flour sample.…”
Section: Discussionmentioning
confidence: 98%
“…Seen from the side of wheat and related cereals, changes in protein composition due to breeding, heat and cold stress, or agricultural practices have been postulated as potential contributors to a higher immunostimulatory potential of modern wheat species compared to landraces and heritage wheats. While protein expression patterns do differ between wheat species, i.e., diploid einkorn, tetraploid emmer, and durum wheat as well as hexaploid spelt and common wheat (177)(178)(179), there are currently too few comparative in vitro or in vivo studies available to allow a precise assessment as to whether these differences might be related to the prevalence of WRDs or not. For example, the 33-mer peptide from α2gliadin that is frequently described as the immunodominant peptide in CD, was only detected in common wheat and spelt, but it was not present in emmer, durum wheat, or einkorn (180).…”
Section: The Increasing Prevalence Of Wheat-related Disordersmentioning
confidence: 99%